Development of a Post-Anesthesia Phase Documentation Feature in the Areme Application for Anesthesiology Nursing Care - Krisna Bayu Tri Pamungkas; Marta Tania Gabriel Ching Cing; Rully Annisa; Endiyono (Asosiasi Dosen Muda Indonesia, 2026)
The rapid advancement of technology requires innovation in anesthesia nursing education, particularly in transitioning conventional documentation of anesthesia nursing care (ASKAN) into electronic formats. To support this need, the AREME application was developed as a tool to assist students in documenting ASKAN across different phases of anesthesia care. Previous versions of the system were limited, as documentation features only covered the intra-anesthesia phase. This study addresses those limitations by expanding the application to include comprehensive documentation from pre-anesthesia through post-anesthesia. Using a Research and Development (R&D) design with a Rapid Application Development (RAD) approach, the study produced new modules and interface improvements. Specifically, a post-anesthesia documentation feature was integrated, enabling outputs that encompass both intra- and post-anesthesia phases. The findings demonstrate that the AREME application has been successfully enhanced to meet user needs, improve documentation completeness, and support more effective recording of anesthesia nursing care.